Preparation method and application of long-acting waterproof concrete admixture

The synergistic effect of hydration regulator A, prepared by the ring-opening addition of organosilicon amine and maleic anhydride, and fluorinated silane copolymer B solves the problems of insufficient construction quality, micro-crack control and long-term stability of existing concrete waterproofing and seepage prevention technologies, and achieves long-term waterproofing and seepage prevention effects for concrete.

CN122277808APending Publication Date: 2026-06-26ANHUI ZHEAN NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610530979.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-21
Publication Date
2026-06-26

Smart Images

  • Figure CN122277808A_ABST
    Figure CN122277808A_ABST
Patent Text Reader

Abstract

This invention belongs to the field of concrete admixtures and functional materials, and discloses a method for preparing a long-lasting waterproof concrete admixture and its application. The method includes: ring-opening addition of an organosilicon amine compound containing amino and trialkoxysilane groups with maleic anhydride in an inert organic solvent to obtain a hydration regulator A containing carboxylic acid groups, amide groups, and trialkoxysilane groups; copolymerizing γ-methacryloyloxypropyltrialkoxysilane with perfluorooctyl acrylate to obtain a bifunctional self-assembled component B; adding A and B to an aqueous phase, dispersing and mixing them in the presence of a dispersant, adjusting the pH, and reacting at 55-70℃ to hydrolyze, condense, and crosslink the trialkoxysilane groups to obtain an aqueous dispersion or emulsion admixture. When incorporated into concrete, this admixture can regulate the hydration process and construct a hydrophobic network in situ, reducing capillary water absorption and permeability, improving impermeability and durability, and is suitable for underground and marine engineering concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of concrete admixtures and functional materials, specifically relating to a method for preparing a long-lasting waterproof concrete admixture and its application. Background Technology

[0002] Concrete, as the most commonly used civil engineering material, is susceptible to water seepage and erosion during its service life. These factors are key causes of durability problems such as steel corrosion, freeze-thaw erosion, sulfate attack, and chloride ion intrusion, especially in underground engineering, marine engineering, and long-term humid environments. Existing concrete waterproofing and seepage prevention technologies mainly include external waterproof membranes or coatings, the addition of inorganic filler-type seepage prevention materials, penetrating crystalline materials, and organosilicon hydrophobic agents. External waterproofing layers are highly dependent on construction quality and are easily affected by substrate cracking, hollowing, or interface peeling, leading to failure. While inorganic fillers and crystalline materials can block pores to a certain extent, their long-term control over microcracks and interface transition zones is limited, and under repeated wet-dry cycles and salt corrosion environments, the pore-blocking products may dissolve or the channels may reconnect. Organosilicon or hydrophobic admixtures can reduce the surface energy of pore walls and inhibit capillary water absorption, but their effective components are prone to migration, leaching, or poor bonding with hydration products in highly alkaline pore solutions, resulting in a decline in waterproofing effectiveness over time. Meanwhile, existing technologies for cement hydration control primarily focus on workability, setting time, or early strength adjustment, while hydrophobic materials mainly focus on surface modification or a single waterproofing function. These two approaches are often independent, lacking an in-situ construction mechanism that coordinates with the hydration process. Furthermore, they still suffer from problems such as antagonism between waterproofing and strength, insufficient long-term effectiveness, and susceptibility to process substitution. Therefore, there is an urgent need to provide a long-lasting waterproof concrete admixture capable of controllable condensation crosslinking and symbiosis with the matrix during hydration, along with its preparation and application methods, to improve the impermeability and durability of concrete. Summary of the Invention

[0003] To address the shortcomings mentioned in the background art, the present invention aims to provide a method for preparing a long-lasting waterproof concrete admixture and its application. A hydration regulator A is prepared by ring-opening addition of organosilicon amine and maleic anhydride, and a copolymer B containing silane and fluorine segments is subjected to controlled hydrolysis, condensation, and crosslinking in an aqueous phase to form a stable hydrophobic network. This achieves synergistic effects of hydration regulation and waterproofing, improving the impermeability and durability of concrete, and is suitable for underground and marine engineering.

[0004] The objective of this invention can be achieved through the following technical solutions: A method for preparing a long-lasting waterproof concrete admixture includes the following steps: Step 1: An organosilicon amine compound containing amino and trialkoxysilane groups is reacted with maleic anhydride in an inert organic solvent to undergo a ring-opening addition reaction, yielding a reaction product containing carboxylic acid group, amide group and trialkoxysilane group, which is used as hydration regulator A. Step 2: γ-methacryloxypropyltrialkoxysilane and perfluorooctyl acrylate are subjected to free radical copolymerization under the action of an initiator to obtain a copolymer containing a trialkoxysilane anchoring group and a fluorinated hydrophobic segment, which is used as the bifunctional self-assembly component B. Step 3: Add the hydration regulator A and the bifunctional self-assembled component B to the aqueous phase, disperse and mix them until uniform in the presence of a dispersant, adjust the pH of the system to a range that is conducive to the hydrolysis and condensation of the trialkoxysilane groups, and react at 55-70°C for 1-5 h to allow the trialkoxysilane groups in the hydration regulator A and the bifunctional self-assembled component B to hydrolyze and further condense and crosslink, thereby obtaining a long-lasting waterproof concrete admixture.

[0005] More preferably, the organosilicone amine compound in step 1 is bis-(3-triethoxysilylpropyl)amine; the molar ratio of the organosilicone amine compound to maleic anhydride is 1:(1.0-1.2).

[0006] More preferably, the inert organic solvent in step 1 is selected from one or more of n-hexane, cyclohexane, and toluene; the reaction temperature is 60–80°C, and the reaction time is 2–6 h.

[0007] More preferably, the hydration regulator A obtained in step 1 includes the ring-opening addition reaction product, as well as the salt and condensation oligomer formed from the reaction product.

[0008] More preferably, in step 2, the molar ratio of γ-methacryloxypropyltrialkoxysilane to perfluorooctyl acrylate is 1:(0.8-1.0); the initiator is azobisisobutyronitrile or benzoyl peroxide, and the amount of initiator is 0.3-1.5 wt% of the total mass of the two monomers; the polymerization temperature is 65-85℃, and the polymerization time is 3-8 h.

[0009] More preferably, after the copolymerization reaction in step 2 is completed, unreacted monomers and solvents are removed by depressurization; the depressurization conditions are an absolute pressure of 5-30 kPa and a temperature of 70-110℃.

[0010] More preferably, in step 3, the hydration regulator A and the bifunctional self-assembled component B have a solid content mass ratio of 1:(1.2-2.5); the dispersant is selected from one or more of polyethylene glycol, polyvinylpyrrolidone, and polycarboxylic acid dispersants, and the amount of dispersant used is 0.5-5 wt% of the total mass of the system; the solid content of the finished additive is 20-45 wt%.

[0011] More preferably, step 3 employs stepwise pH control to achieve controlled hydrolysis and condensation crosslinking: first, the pH of the system is adjusted to 4.0–6.0 for pre-hydrolysis for 0.2–2 h, and then the pH of the system is adjusted to 7.0–9.0 for condensation crosslinking for 0.5–4 h.

[0012] A long-lasting waterproof concrete admixture, wherein the admixture is an aqueous dispersion or emulsion, and its solid contents include the following components in parts by weight: 10-45 parts of hydration regulator A, 30-90 parts of bifunctional self-assembled component B, 0.5-10 parts of dispersant, and 0-10 parts of optional additives.

[0013] A method for applying a long-lasting waterproof concrete admixture involves adding the admixture to a concrete mixture at 0.3–2.5 wt% of the total mass of the concrete cementitious materials for use in underground or marine engineering concrete. The admixture is premixed with the mixing water before being added to the mixing equipment, or added simultaneously with the mixing water and stirred until homogeneous.

[0014] The beneficial effects of this invention are: The long-lasting waterproof concrete admixture of this invention achieves the technical effect of actively forming an impermeable structure from the inside of concrete through the synergistic construction of "hydration regulator A - fluorinated silane copolymer B". Hydration regulator A is obtained by ring-opening addition of organosilicon amine and maleic anhydride. The molecule simultaneously introduces hydrophilic polar sites such as carboxylic acid groups and amide groups, as well as trialkoxysilane groups. On the one hand, it can adsorb and interact with the surface of cement particles and the hydration ion system in a high-alkalinity pore solution environment, regulate the early hydration process and the rhythm of hydration product formation, promote more continuous and denser CSH gel, reduce capillary connectivity from the source and improve the structure of the interface transition zone. On the other hand, its trialkoxysilane groups and the trialkoxysilane groups in component B are controlled to hydrolyze in the aqueous phase to generate silanol, and further condense under suitable pH and temperature conditions to form a cross-linked network of Si-O-Si bonds. This makes the waterproof phase no longer a simple physical admixture or a migratable hydrophobic agent, but rather fixed in situ in the microstructure of the cement matrix in a chemically bonded and networked form, significantly improving the resistance to leaching, migration and durable cycle stability. Component B is obtained by copolymerizing silane-containing monomers with perfluorooctyl acrylate. The fluorinated hydrophobic segments have extremely low surface energy and can form a stable hydrophobic interface in the pore walls and micropore channels, inhibiting capillary water absorption and the continuity of the permeable water film. This further weakens the driving force of water transport while maintaining the overall density of the concrete structure. Attached Figure Description

[0015] The invention will now be further described with reference to the accompanying drawings.

[0016] Figure 1 The graph shows the impermeability retention rate of concrete specimens prepared for the examples and comparative examples after 0-30 cycles of wet and dry aging. Detailed Implementation

[0017] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0018] Example 1: Verification that the additive of the present invention can still be stably prepared under conditions of low reaction intensity and low doping parameters, and achieve a long-lasting waterproof system of silane hydrolysis condensation crosslinking network.

[0019] Step 1: Add 72.2 g of bis-(3-triethoxysilylpropyl)amine to a 250 mL three-necked flask, add 10.0 g of n-hexane as an inert organic solvent, stir under nitrogen protection and heat to 60 °C; add 16.6 g of maleic anhydride to make the molar ratio of bis-(3-triethoxysilylpropyl)amine to maleic anhydride 1:1.0, maintain the reaction at 60 °C for 2 h, cool to room temperature after the reaction is completed, remove n-hexane under reduced pressure to obtain the ring-opening addition reaction product, which contains carboxylic acid group, amide group and triethoxysilyl group, and serves as hydration regulator A.

[0020] Step 2: 47.2 g of γ-methacryloxypropyltrialkoxysilane and 63.6 g of perfluorooctyl acrylate (1H,1H,2H,2H-perfluorooctyl acrylate) were added to a 500 mL reaction flask to make a molar ratio of 1:0.8. 0.33 g of azobisisobutyronitrile (0.3 wt% of the total mass of the two monomers) was added. The mixture was stirred under nitrogen protection and heated to 65 °C. The polymerization reaction was maintained at 65 °C for 3 h. After the reaction was completed, the unreacted monomers and residual volatiles were removed under reduced pressure at 70 °C and 5 kPa for 1 h. The copolymer containing a trialkoxysilane anchoring group and a fluorinated hydrophobic segment was obtained by cooling and used as bifunctional self-assembled component B.

[0021] Step 3: Add 800.0 g of deionized water and 5.0 g of polyethylene glycol dispersant to a 1.5 L stirred tank and stir until dissolved. Then add 88.8 g of hydration regulator A and 106.4 g of bifunctional self-assembled component B, so that the solid content of A to B is 1:1.2. At the same time, adjust the solid content of the finished admixture to 20 wt%. Continue stirring and dispersing in the presence of the dispersant until the system is uniform. First, adjust the pH of the system to 4.0 with an acidic regulator and pre-hydrolyze at 55℃ for 0.2 h. Then, adjust the pH of the system to 7.0 with an alkaline regulator and condense and crosslink at 55℃ for 0.5 h. The total reaction time is 1 h, which allows the trialkoxysilane groups in hydration regulator A and bifunctional self-assembled component B to hydrolyze and further condense and crosslink. After the reaction is completed, cool to room temperature and filter to remove a small amount of insoluble matter to obtain the long-lasting waterproof concrete admixture.

[0022] Example 2: Verification that the additive of the present invention can still be stably prepared and form a denser silicon-oxygen crosslinked network under conditions of higher reaction temperature, higher monomer ratio and higher solid content.

[0023] Step 1: Add 72.2 g of bis-(3-triethoxysilylpropyl)amine to a 250 mL three-necked flask, add 20.0 g of toluene as an inert organic solvent, stir under nitrogen protection and heat to 80 °C; add 19.9 g of maleic anhydride to make the molar ratio of bis-(3-triethoxysilylpropyl)amine to maleic anhydride 1:1.2, maintain the reaction at 80 °C for 6 h, cool to room temperature after the reaction is completed, remove toluene under reduced pressure to obtain the ring-opening addition reaction product, which contains carboxylic acid group, amide group and triethoxysilyl group, and serves as hydration regulator A.

[0024] Step 2: 49.7 g of γ-methacryloxypropyltrialkoxysilane and 83.6 g of 1H,1H,2H,2H-perfluorooctyl acrylate were added to a 500 mL reaction flask to make a molar ratio of 1:1.0. 2.00 g of benzoyl peroxide (1.5 wt% of the total mass of the two monomers, 133.3 g) was added. The mixture was stirred under nitrogen protection and heated to 85 °C, and the polymerization reaction was maintained at 85 °C for 8 h. After the reaction was completed, unreacted monomers and residual volatiles were removed under reduced pressure at 110 °C and 30 kPa for 1 h. After cooling, a copolymer containing a trialkoxysilane anchoring group and a fluorinated hydrophobic segment was obtained as the bifunctional self-assembled component B.

[0025] Step 3: Add 421.7 g of deionized water and 30.0 g of polycarboxylate dispersant to a stirred tank and stir until dissolved. Then add 90.0 g of hydration regulator A and 225.0 g of bifunctional self-assembled component B, so that the solid content of A to B is 1:2.5, and adjust the solid content of the finished admixture to 45 wt%. Continue stirring and dispersing in the presence of the dispersant until the system is uniform. First, adjust the pH of the system to 6.0 with an acidic regulator and pre-hydrolyze at 70℃ for 2 h. Then, adjust the pH of the system to 9.0 with an alkaline regulator and condense and crosslink at 70℃ for 3 h, so that the trialkoxysilane groups in hydration regulator A and bifunctional self-assembled component B undergo hydrolysis and further condensation and crosslinking. After the reaction is completed, cool to room temperature and filter to remove a small amount of insoluble matter to obtain the long-lasting waterproof concrete admixture.

[0026] Example 3: An admixture was prepared under the condition that all parameters were at an intermediate level, serving as a representative sample for performance and process stability.

[0027] Step 1: Add 72.2 g of bis-(3-triethoxysilylpropyl)amine to a 250 mL three-necked flask, add 15.0 g of cyclohexane as an inert organic solvent, stir under nitrogen protection and heat to 70 °C; add 18.2 g of maleic anhydride to make the molar ratio of bis-(3-triethoxysilylpropyl)amine to maleic anhydride 1:1.1, maintain the reaction at 70 °C for 4 h, cool to room temperature after the reaction is completed, remove cyclohexane under reduced pressure to obtain the ring-opening addition reaction product, which contains carboxylic acid group, amide group and triethoxysilyl group, and serves as hydration regulator A.

[0028] Step 2: 47.2 g of γ-methacryloxypropyltrialkoxysilane and 71.5 g of 1H,1H,2H,2H-perfluorooctyl acrylate were added to a 500 mL reaction flask to make a molar ratio of 1:0.9. 1.07 g of azobisisobutyronitrile (0.9 wt% of the total mass of the two monomers, 118.7 g) was added. The mixture was stirred under nitrogen protection and heated to 75 °C. The polymerization reaction was maintained at 75 °C for 5.5 h. After the reaction was completed, unreacted monomers and residual volatiles were removed under reduced pressure at 90 °C and 17.5 kPa for 1 h. After cooling, a copolymer containing a trialkoxysilane anchoring group and a fluorinated hydrophobic segment was obtained as the bifunctional self-assembled component B.

[0029] Step 3: Add 675.0 g of deionized water and 27.5 g of polyvinylpyrrolidone dispersant (2.75 wt% of the total system mass) to a 2 L stirred tank and stir until dissolved. Then add 90.4 g of hydration regulator A and 167.2 g of bifunctional self-assembled component B, making the solid content ratio of A to B 1:1.85. Add deionized water to adjust the solid content of the additive to 32.5 wt%. Continue stirring and dispersing in the presence of the dispersant until the system is homogeneous. First, adjust the pH of the system to 5.0 with an acidic regulator and pre-hydrolyze at 62.5℃ for 1.1 h. Then, adjust the pH of the system to 8.0 with an alkaline regulator and condense and crosslink at 62.5℃ for 1.9 h. This allows the trialkoxysilane groups in hydration regulator A and bifunctional self-assembled component B to hydrolyze and further condense and crosslink. The total reaction time is 3.0 h. h, after the reaction is complete, cool to room temperature and filter to remove a small amount of insoluble matter to obtain the long-lasting waterproof concrete admixture.

[0030] Comparative Example 1: This comparative example does not involve the ring-opening addition reaction of organosilicon amine compounds with maleic anhydride, does not prepare hydration regulator A, and does not add hydration regulator A in subsequent preparation processes.

[0031] Step 1: 47.2 g of γ-methacryloxypropyltrialkoxysilane and 71.5 g of 1H,1H,2H,2H-perfluorooctyl acrylate were added to a 500 mL reaction flask to make a molar ratio of 1:0.9. 1.07 g of azobisisobutyronitrile (0.9 wt% of the total mass of the two monomers) was added. The mixture was stirred under nitrogen protection and heated to 75 °C. The polymerization reaction was maintained at 75 °C for 5.5 h. After the reaction was completed, the unreacted monomers and residual volatiles were removed under reduced pressure at 90 °C and 17.5 kPa for 1 h. After cooling, a copolymer containing a trialkoxysilane anchoring group and a fluorinated hydrophobic segment was obtained as the bifunctional self-assembled component B.

[0032] Step 2: Add 675.0 g of deionized water and 27.5 g of polyvinylpyrrolidone dispersant to a stirred tank and stir until dissolved. Then add 167.2 g of bifunctional self-assembled component B and add 130.3 g of deionized water to make the total mass of the system about 1000 g. Continue stirring and dispersing in the presence of the dispersant until the system is uniform. First, adjust the pH of the system to 5.0 with an acidic regulator and pre-hydrolyze at 62.5℃ for 1.1 h. Then, adjust the pH of the system to 8.0 with an alkaline regulator and condense and crosslink at 62.5℃ for 1.9 h to hydrolyze and further condense and crosslink the trialkoxysilane groups in component B. The total reaction time is 3.0 h. After the reaction is completed, cool to room temperature and filter to remove a small amount of insoluble matter to obtain a comparative long-lasting waterproof concrete admixture.

[0033] Comparative Example 2: Under the condition of keeping the hydration regulator A and the preparation process unchanged, the fluorinated acrylate monomer in component B was replaced with n-octyl acrylate in equal molar amounts to verify the effect of the fluorinated hydrophobic segment on long-term hydrophobicity and impermeability stability.

[0034] Step 1: Add 72.2 g of bis-(3-triethoxysilylpropyl)amine to a 250 mL three-necked flask, add 15.0 g of cyclohexane as an inert organic solvent, stir under nitrogen protection and heat to 70 °C; add 18.2 g of maleic anhydride to make the molar ratio of bis-(3-triethoxysilylpropyl)amine to maleic anhydride 1:1.1, maintain the reaction at 70 °C for 4 h, cool to room temperature after the reaction is completed, remove cyclohexane under reduced pressure to obtain the ring-opening addition reaction product, which is used as hydration regulator A.

[0035] Step 2: 47.2 g of γ-methacryloxypropyltrialkoxysilane and 47.5 g of n-octyl acrylate were added to a 500 mL reaction flask to make a molar ratio of 1:0.9. 0.85 g of azobisisobutyronitrile (0.9 wt% of the total mass of the two monomers, 94.7 g) were added. The mixture was stirred under nitrogen protection and heated to 75 °C. The polymerization reaction was maintained at 75 °C for 5.5 h. After the reaction was completed, unreacted monomers and residual volatiles were removed under reduced pressure at 90 °C and 17.5 kPa for 1 h. The copolymer containing the trialkoxysilane anchoring group and the n-octyl hydrophobic segment was obtained by cooling and was used as component B′ of Comparative Example 2.

[0036] Step 3: Add 675.0 g of deionized water and 27.5 g of polyvinylpyrrolidone dispersant to a mixing tank and stir until dissolved. Then add 90.4 g of hydration regulator A and 167.2 g of component B′, and add 122.8 g of deionized water to make the total mass of the system about 1000 g. Continue stirring and dispersing in the presence of the dispersant until the system is uniform. First, adjust the pH of the system to 5.0 with an acidic regulator and pre-hydrolyze at 62.5℃ for 1.1 h. Then, adjust the pH of the system to 8.0 with an alkaline regulator and condense and crosslink at 62.5℃ for 1.9 h, so that the trialkoxysilane groups in hydration regulator A and component B′ will be hydrolyzed and further condensed and crosslinked. The total reaction time is 3.0 h. After the reaction is completed, cool to room temperature and filter to remove a small amount of insoluble matter to obtain a comparative long-lasting waterproof concrete admixture.

[0037] Performance testing 1. Slump and time-lapse test The concrete mix proportions of each group were consistent. Admixture samples were added at a mass fraction of 1.2% of the cementitious materials. After mixing for 3 minutes, the mixture was allowed to stand for 1 minute, then mixed again for 1 minute. The mixing time was considered 0 h. Samples were then placed in a slump cone (filled in three layers, each layer compacted 25 times). After filling and leveling, the slump cone was lifted vertically and steadily to measure the initial slump S0. The samples were placed in an environment of 20±2℃ and relative humidity ≥50%, covered to prevent water loss, and the slump S1 and S2 were measured after rapid re-mixing for 30 seconds at 1 h and 2 h, respectively. The slump loss rate over time was calculated as: Δt=(S0−St) / S0×100%, where: Δt: slump loss rate over time, S0: initial slump, St: slump at time t. The results are shown in Table 1 below.

[0038] Table 1 Slump and Time-Related Loss Rate

[0039] As shown in Table 1, the initial slump of the concrete in each group was between 182 and 190 mm, indicating that the introduction of the admixture did not significantly adversely affect the initial workability of the mixture. However, with the extension of the standing time, the slump decay of Examples 1-3 was significantly lower than that of the comparative examples. The loss rate of Examples 1 was only 6.3%-7.0% at 1 h and 11.2%-13.5% at 2 h, while Comparative Examples 1 and 2 reached 23.1% and 20.4% respectively at 2 h, showing a faster fluidity decay. The results show that the admixture system of the present invention can effectively delay slump loss while maintaining initial fluidity, demonstrating better dispersion stability and slump retention performance. Among them, Example 3 maintained 167 mm at 2 h, showing the best overall performance, indicating that the synergistic network formation of hydration regulator A and fluorinated component B helps to improve the time stability of the mixture.

[0040] 2. Compressive strength test Concrete compressive strength was tested according to GB / T 50081. The mix proportions were consistent across groups, with admixtures added at 1.2% of the cementitious material mass. The mixing process was the same as for the slump test. Triple molds (100 mm × 100 mm × 100 mm) were used, with at least three specimens per group. After compaction on a vibrating table, the molds were leveled and cured under a film for 24 hours before demolding. After demolding, the specimens were placed in a standard curing room at (20±2)℃ and relative humidity ≥95% for 7 days and 28 days. During the compressive strength test, a continuous and uniform loading rate was applied, and the average strength of the three specimens was taken. The results are shown in Table 2 below.

[0041] Table 2 Compressive Strength

[0042] As shown in Table 2, the compressive strength of each group at 7 days and 28 days increased with age, but the example groups were generally superior to the comparative groups. Examples 1-3 had compressive strengths of 42.0-44.0 MPa at 7 days, higher than the 39.0 MPa of comparative example 1, indicating that the introduction of hydration regulator A facilitated the early formation of hydration products and structural densification, thereby improving early load-bearing capacity. At 28 days, the examples reached 55.0-57.5 MPa, an increase of approximately 9%-15% compared to comparative example 1, and not lower than comparative example 2 (54.0 MPa), demonstrating that the present invention achieved hydrophobic and impermeable effects without causing strength loss, but rather achieved a synergistic improvement in strength.

[0043] 3. Impermeability test The concrete impermeability was tested using the stepwise pressure penetration height method. All concrete mix proportions were consistent, with admixtures added at 1.2% of the cementitious material mass. Mixing and molding processes were identical. Standard impermeability test molds were used to form specimens, which were vibrated to compact and level the surface. After curing with a membrane for 24 hours, the specimens were demolded and then placed in an environment of (20±2)℃ and relative humidity ≥95% for 28 days. Before testing, the sides of the specimens were sealed. After being placed in the impermeability tester, the pressure was increased stepwise according to the standard procedure to the set water pressure and maintained. After pressure maintenance, the specimens were split open, and the maximum seepage height was measured and recorded. At least three specimens were tested in each group, and the average value was taken. The results are shown in Table 3 below.

[0044] Table 3. Permeability height after 28 days

[0045] Table 3 shows that the permeation height of the specimens in each group at 28 days of age differed significantly. The overall permeation height of the example group was significantly lower than that of the comparative example group, indicating that the admixture of the present invention can effectively reduce the connectivity of concrete seepage channels and improve impermeability. The permeation height of Examples 1 to 3 was 6.0–8.5 mm, with Examples 2 and 3 being 6.0 mm and 6.5 mm, respectively. This represents a reduction of approximately 53%–57% compared to 14.0 mm in Comparative Example 1 and approximately 23%–45% compared to 11.0 mm in Comparative Example 2, demonstrating the seepage suppression advantage brought about by the synergistic effect of hydration regulator A and fluorinated component B. Comparative Example 1 lacked hydration regulator A, resulting in insufficient densification of the pore structure and thus the highest permeation height. Although Comparative Example 2 contained A, the hydrophobic segment was changed from fluorinated to n-octyl, weakening the hydrophobic interface stability and capillary flow suppression ability, thus its impermeability improvement was not as good as that of the examples.

[0046] 4. Capillary water absorption coefficient test The concrete mix proportions were consistent across all groups, with admixtures added at 1.2% of the cementitious material mass. Standard curing was performed for 28 days. Specimens were cut into 100 mm × 100 mm × 50 mm pieces, dried at 50℃ to constant weight, and after cooling, the sides and top surface were sealed, leaving only the bottom surface exposed to water. The specimens were immersed in a shallow water pan to a depth of 2–3 mm, and their mass was measured at 1 h, 3 h, 6 h, and 24 h. Water absorption per unit area was calculated using I = Δm / A, and a linear fit was performed on I against t0.5, with the slope representing the capillary absorption coefficient S. The results are shown in Table 4 below.

[0047] Table 4. Capillary water absorption coefficient 28 days

[0048] Table 4 shows that the capillary water absorption coefficients of the specimens in each group differed significantly. The overall values ​​of the Example Group were significantly lower than those of the Comparative Group, indicating that the additive of the present invention can effectively inhibit capillary water rise and absorption rate. The S values ​​of Examples 1 to 3 ranged from 0.16 to 0.22 kg·m⁻²·h⁻⁰.⁵, with Example 2 having the lowest value (0.16) and Example 3 having a value of 0.18, which is about 37% to 54% lower than that of Comparative Example 1 (0.35) and about 21% to 43% lower than that of Comparative Example 2 (0.28). This indicates that the synergistic effect of hydration regulator A and fluorinated hydrophobic segment component B can form a more stable hydrophobic interface on the pore wall and reduce pore connectivity, thereby significantly weakening the capillary water absorption driving force. Comparative Example 1 lacked A, resulting in insufficient pore structure densification, making it easier for capillary channels to form a continuous water film, and thus having the highest water absorption coefficient. Although Comparative Example 2 contained A, its hydrophobic segments did not contain fluorine, resulting in a weaker surface energy effect and hydrophobic stability, and its effect of inhibiting capillary water absorption was not as good as that of the Examples.

[0049] 5. Test of impermeability retention rate after wet and dry aging cycles The concrete mix proportions were consistent across all groups, with admixtures added at 1.2% of the cementitious material mass. The specimens were molded using impermeability test molds and cured to standard for 28 days before initial impermeability grade testing (initial impermeability grade P0). Subsequently, the same batch of specimens underwent accelerated aging via wet-dry cycles: specimens were immersed in clean water at 20±2℃ for 24 hours, then removed and dried in an oven at 50±2℃ for 24 hours, constituting one cycle, for a total of 30 cycles. After each cycle, the specimens were allowed to recover at 20±2℃ for 24 hours, and the aging impermeability grade P1 was determined using the same method. Performance retention rate was calculated as η = P1 / P0 × 100%, with the average value of three specimens from each group taken. The results are shown in Table 5 below.

[0050] Table 5. Permeability retention rate after 30 wet-dry cycles

[0051] As shown in Table 5, the impermeability of all groups of specimens decreased after 30 wet-dry cycles of aging. However, the retention rate of the example group was significantly higher than that of the comparative group, demonstrating the long-term impermeability advantage of the admixture of this invention. The initial impermeability grades of Examples 1-3 were P12-P14, and after aging, they remained at P10-P12, with a retention rate of 83%-86%. In contrast, the retention rate of Comparative Example 1 decreased from P10 to P6, with a retention rate of only 60%, and that of Comparative Example 2 decreased from P12 to P8, with a retention rate of 67%. The results indicate that the synergistic effect of hydration regulator A and fluorine-containing component B can construct a more stable silica-oxygen cross-linked hydrophobic network at the interface between the concrete pore wall and hydration products, reducing the migration and leaching of active components, slowing down the reconnection of pores and the restoration of seepage pathways caused by wet-dry cycles, thereby maintaining a high impermeability grade under long-term cyclic action.

[0052] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0053] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.

Claims

1. A method for preparing a long-lasting waterproofing concrete admixture, characterized by, Includes the following steps: Step 1: An organosilicon amine compound containing amino and trialkoxysilane groups is reacted with maleic anhydride in an inert organic solvent to undergo a ring-opening addition reaction, yielding a reaction product containing carboxylic acid group, amide group and trialkoxysilane group, which is used as hydration regulator A. Step 2: γ-methacryloxypropyltrialkoxysilane and perfluorooctyl acrylate are subjected to free radical copolymerization under the action of an initiator to obtain a copolymer containing a trialkoxysilane anchoring group and a fluorinated hydrophobic segment, which is used as the bifunctional self-assembly component B. Step 3: Add the hydration regulator A and the bifunctional self-assembled component B to the aqueous phase, disperse and mix them until uniform in the presence of a dispersant, adjust the pH of the system to a range that is conducive to the hydrolysis and condensation of the trialkoxysilane groups, and react at 55-70°C for 1-5 h to allow the trialkoxysilane groups in the hydration regulator A and the bifunctional self-assembled component B to hydrolyze and further condense and crosslink, thereby obtaining a long-lasting waterproof concrete admixture.

2. The method for preparing a long-lasting waterproof concrete admixture according to claim 1, characterized in that, The organosilane amine compound mentioned in step 1 is bis-(3-triethoxysilylpropyl)amine; the molar ratio of the organosilane amine compound to maleic anhydride is 1:(1.0~1.2).

3. The preparation method of the long-lasting waterproof concrete admixture according to claim 1, characterized in that, The inert organic solvent used in step 1 is selected from one or more of n-hexane, cyclohexane, and toluene; the reaction temperature is 60–80°C, and the reaction time is 2–6 h.

4. The preparation method of the long-lasting waterproof concrete admixture according to claim 1, characterized in that, The hydration regulator A obtained in step 1 includes the ring-opening addition reaction product, as well as the salt and condensation oligomer formed from the reaction product.

5. The preparation method of the long-lasting waterproof concrete admixture according to claim 1, characterized in that, In step 2, the molar ratio of γ-methacryloxypropyltrialkoxysilane to perfluorooctyl acrylate is 1:(0.8-1.0); the initiator is azobisisobutyronitrile or benzoyl peroxide, and the amount of initiator is 0.3-1.5 wt% of the total mass of the two monomers; the polymerization temperature is 65-85℃, and the polymerization time is 3-8 h.

6. The preparation method of the long-lasting waterproof concrete admixture according to claim 1, characterized in that, After the copolymerization reaction in step 2 is completed, unreacted monomers and solvents are removed by depressurization; the depressurization conditions are an absolute pressure of 5-30 kPa and a temperature of 70-110℃.

7. The preparation method of the long-lasting waterproof concrete admixture according to claim 1, characterized in that, In step 3, the hydration regulator A and the bifunctional self-assembled component B are in a solid mass ratio of 1:(1.2-2.5); the dispersant is selected from one or more of polyethylene glycol, polyvinylpyrrolidone, and polycarboxylic acid dispersants, and the amount of dispersant is 0.5-5 wt% of the total mass of the system; the solid content of the finished additive is 20-45 wt%.

8. The preparation method of the long-lasting waterproof concrete admixture according to claim 1, characterized in that, Step 3 employs stepwise pH control to achieve controlled hydrolysis and condensation crosslinking: first, the pH of the system is adjusted to 4.0–6.0 for pre-hydrolysis for 0.2–2 h, and then the pH of the system is adjusted to 7.0–9.0 for condensation crosslinking for 0.5–4 h.

9. A long-lasting waterproof concrete admixture prepared by the method according to any one of claims 1 to 8, characterized in that, The additive is an aqueous dispersion or emulsion, and its solid content includes the following components in parts by weight: 10-45 parts of hydration regulator A, 30-90 parts of bifunctional self-assembled component B, 0.5-10 parts of dispersant, and 0-10 parts of optional auxiliary agent.

10. A method for applying the long-lasting waterproof concrete admixture as described in claim 9, characterized in that, The admixture is added to the concrete mixture at a ratio of 0.3 to 2.5 wt% of the total mass of the concrete cementitious materials for use in underground or marine engineering concrete. The admixture is premixed with the mixing water before being added to the mixing equipment, or added simultaneously with the mixing water and stirred until uniform.